Construção de sistema eletroquímico com eletrodo circular para síntese de Polímeros Intrinsecamente Condutores: PIC's - Santos, Fábio Cândido dos (2015)
This work involves the construction of a portable equipment device for electrochemical polymerization of an Intrinsically Conductive Polymer - PIC. Using a rotary circular electrode, this method’all allows the production of various polymers especialy PIC's parameterize, controlling and monitoring all the process, so that a polymer can be prepared with maximum efficiency. As it is a portable equipment, it is possible to share with the universities labs and research centers that are working with conductive polymers and or other tips of polymers with can be inter interested in electrochemical synthesis. Using this method, you can ensuring the well contours specified parameters, the produced quantity for the preparation of the tests are larger, allowing a better characterization of the samples and production of products. The studied Conductive Polymer for the qualification of portable equipment was Polyaniline "PAni", this was characterized by the Fourier transform infrared region - FTIR, scanning electron microscopy – SEM, spectroscopy ultraviolet and Visible - UVVIS, thermogravimetric analysis – TGA, analysis by cyclic voltammetric and conductivity volumetric by the method at two tips.